Characteristics of Distinct University Teaching Staff as an Index of Higher Education Quality in Jordan - Alaa Zuher Alrwashdeh; Asma Rebhe Alarab (University of Science and Technology, Yemen, 2016)
Abstract: This study aimed at identifying the characteristics of distinct university teaching staff as an index  of higher education quality from social sciences students viewpoint  in Al Balqa applied university in light of sex and specialty variables .To achieve the study goals a descriptive Approach in addition to social survey approach  were used .A questionnaire was applied on a sample of (302) students to collect information .The study concluded that : there are some characteristics distinguishes distinct  teaching staff some of them related to academic aspect , some to the social aspect and others are related to psychological aspect .The study also concluded that the most important characteristics from the students viewpoint  are the academic ones which includes :being faith to work ,duties understanding , seriousness in teaching , respect  students opinions ,and time respect and commitment ,followed by social characteristics which includes : leadership, good relations with students, gentleness ,  cooperative, finally comes the psychological aspect :comfortable , easy to communicate with ,patience,  equanimity  , and good listener. The study results also pointed out there are no statically  significant differences in distinct   university teaching staff  characteristics related to sex variable and specialty variables on the psychological characteristics pivot , while the results showed statically significant  differences  due to social and academic characteristics and the whole tool related to specialty variable in favor of deviance  and crime  specialty In light of the above mentioned results the study recommended some theoretical and practical recommendations .